Recommender System: Revolution in E-Commerce (International Journal of Engineering and Computer Science, 2015)
With the growing expansion of information on World Wide Web, web sites are facing challenges to meet their customers’ needs to present them with the information they are interested in. Recommender systems have emerged as a solution to this issue. Recommender system makes predictions for the users based on the analysis of their past behaviour. It is majorly classified in three categories which include: content based collaborative filtering and hybrid recommender system. Recommender systems have become an integral part of internet. They are becoming popular in the area of data mining, information filtering and e-commerce. In this paper, we have presented our study of various recommender techniques. We have also described the limitations of various recommendation techniques